The effectiveness of a supplementary reading programme for children in Malaysia's rmote schools - Mohd. Asraf, Ratnawati; Abu Kassim, Noor Lide; Sheikh Ahmad, Ismail; Abdul Rahman, Zainurin (2013)
Providing access to quality education should be viewed as a social responsibility. And the backbone of a good education system lies in its ability to promote literacy among the community, particularly the children. This paper reports the findings of a study conducted to evaluate the effectiveness of a supplementary reading programme conducted in remote schools in the states of Sabah and Sarawak, Malaysia. The result suggest that the supplementary reading programme has improved the students' attitudes towards reading, motivated them to read extensively and improved their reading habits.